Ionospheric D Region Remote Sensing Using ELF Sferic Group Velocity. Issue 23 (13th December 2018) - Gołkowski, M.; Sarker, S. R.; Renick, C.; Moore, R. C.; Cohen, M. B.; Kułak, A.; Młynarczyk, J.; Kubisz, J.
Abstract: The lowest region of the ionosphere, the D region, plays an important role in magnetosphere‐ionosphere coupling but is challenging to directly observe. The group velocity of the extremely low frequency (ELF; 3–300 Hz) portion of lightning induced electromagnetic radiation can be used to diagnose the D region electron density profile. Day‐night conditions can be assessed using ELF receivers and lightning detection networks. Analytical formulations and the Long Wave Propagation Capability software package show that ELF group velocity has particular sensitivity to the sharpness of the exponential electron density profile. Applying the technique to sudden ionospheric disturbances shows that the group velocity increases in response to incidence of solar X‐ray flux . A small number of ELF receivers can provide a large‐scale diagnostic of the D region. ELF remote sensing using lightning is complementary to very low frequency remote sensing and can be used to assess the Earth‐ionosphere propagation channel for very low frequency transmitters. Plain Language Summary: The lowest part of the upper atmosphere, the ionospheric D region, is where the plasma state of outer space begins and is important for space physics research. Unfortunately, this layer of the atmosphere is very difficult to measure directly. It is too high for airplanes and balloons, too low for satellites, and not dense enough for direct radio sounding. The only reliable approach is remote sensing using low‐frequency waves. We present a new technique to remotely sense this region using the electromagnetic waves from lightning. The new technique is complementary to existing approaches and can improve accuracy while providing global coverage. Improved diagnosis of this region has impact on a wide range of near‐Earth space research. Key Points: ELF sferic group velocity changes with ionospheric D region conditions Numerical modeling elucidates ELF group velocity dependence on ionospheric profile ELF sferics can be used as a complementary technique to VLF remote sensing